PAKET EDUKASI KEPADA ANAK USIA PRA SEKOLAH DI TK KEENAN KAMPUNG BABAKAN TANGERANG - Yenni Ferawati Sitanggang; Lia Kartika; Riama Marlyn Sihombing; Shinta Yuliana Hasibuan (P3M Universitas Aisyiyah Surakarta, 2022)
The development in a country in the globalization era has grown so fast, many things can be done with sophisticated and modern technology which ease every society without access difficulty. One of the technologies owned by all society is gadget such as smartphones or tablet phones. The technology that sophisticated ease everyone to access any newest and updated knowledge. Many education facilities used gadgets as their media of learning. However, that also brings some bad impacts to many ages if it used irresponsibly such as pornography or even become addicted to children. Not only that, sometimes through gadgets, but children are also exposed to pornography sites and bullying. Therefore, the Faculty of Nursing UPH giving an education package about digital printing, bullying, sex education to children, and their parents in TK Keenan Kampung Babakan, Tangerang.Â At the end of education, children can mention what actions need to be taken when the child is teased by their school friends. The child is also able to mention which body areas can be touched and which body areas must be protected through movement and song.